The Cytotoxic Activity of Marine Sponge-Derived Fungus Aspergillus nomius NC06 Against HT29 Colon Cancer Cells: Cytotoxic Activity of A. nomius NC06 Against HT29 Cancer Cells - Artasasta, Muh. Ade; Djamaan, Akmal; Yanwirasti, Yanwirasti; Taher, Muhammad; Djamaludin, Heder; Siswanto, Siswanto; Handayani, Dian (Journal of Tropical Life Science, 2024)
The study of natural products from marine-derived fungi has been interesting tense to researchers as drug discovery sources. Marine fungus from West Sumatera, Indonesia repeatedly showed their potential for cytotoxic and antimicrobial activities. This study aims to determine the cytotoxic activity against HT29 colon cancer cells of each fraction of ethyl acetate extracts from Aspergillus nomius NC06 derived from marine sponge Neopetrosia chaliniformis. A. nomius was cultivated with rice as a growth medium and extracted with ethyl acetate solvent and evaporated in vacuo to obtain ethyl acetate extract. Furthermore, the compounds of ethyl acetate extract were separated with the VLC (Vacuum Liquide Chromatography) method. Five fractions were obtained, which further investigated their cytotoxic activity against HT29 colon cancer cells by using an MTT assay. The result showed that fractions I and III were categorized as potential fractions due to their IC50 value of 13.12 ± 0.39 μg/mL and 2.59 ± 0.19 μg/mL, respectively. It was also supported by ANOVA to measure the effect of each concentration (0.1; 1; 10; 100 μg/mL) of each fraction on the viability percentage of HT29 cells with p < 0.005.